Developing Preschool Education: Promoting and Preventing Factors - Kulikovskaya I.E., (Психолого-педагогические исследования, 2019)
The article defines the concept of “developing STEAM-education of children” as a single focused process of upbringing and education, providing the child with knowledge, understanding and assignment of value categories, on the basis of which he develops ways of behavior in the modern world. Natural sciences, technologies, engineering, art and mathematics act as a space for the development of the worldview of preschool children. Determination of the common ground of these areas determines the harmonization of the development of children in modern space. It is suggested that children need to be taught to cope with unexpected situations and solve problems that they have not encountered before, on the basis of value categories that act as phenomena of the child’s consciousness. The space of developing STEAM-education of children is a space of freedom: creativity (artistic, speech, technical), self-expression and self-presentation.